Pretreatment with Group II Metabotropic Glutamate Receptor Agonist LY379268 Protects Neonatal Rat Brains from Oxidative Stress in an Experimental Model of Birth Asphyxia - Bratek, Ewelina (Brain Sci, 2018)
Hypoxia-ischemia (H-I) at the time of birth may cause neonatal death or lead to persistent brain damage. The search for an effective treatment of asphyxiated infants has not resulted in an effective therapy, and hypothermia remains the only available therapeutic strategy. Among possible experimental therapies, the induction of ischemic tolerance is promising. Recent investigations have shown that activation of group II metabotropic glutamate receptors (mGluR2/3) can provide neuroprotection against H-I, but the mechanism of this effect is not clear. The aim of this study was to investigate whether an mGluR2/3 agonist applied before H-I reduces brain damage in an experimental model of birth asphyxia and whether a decrease in oxidative stress plays a role in neuroprotection. Neonatal H-I on seven-day-old rats was used as an experimental model of birth asphyxia. Rats were injected intraperitoneally with the mGluR2/3 agonist LY379268 24 or 1 h before H-I (5 mg/kg). LY379268 reduced the infarct area in the ischemic hemisphere. Application of the agonist at both times also reduced the elevated levels of reactive oxygen species (ROS) in the ipsilateral hemisphere observed after H-I and prevented the increase in antioxidant enzyme activity in the injured hemisphere. The decrease in glutathione (GSH) level was also restored after agonist application. The results suggest that the neuroprotective mechanisms triggered by the activation of mGluR2/3 before H-I act through the decrease of glutamate release and its extracellular concentration resulting in the inhibition of ROS production and reduction of oxidative stress. This, rather than induction of ischemic tolerance, is probably the main mechanism involved in the observed neuroprotection.